A experiência dos agentes socioeducativos em uma unidade de internação para adolescentes em conflito com a lei, em Mato Grosso - Vaillant, Camila Brito (2017)
This study analyzed the experience of socio-educational agents based on their work in a Socioeducational Center for adolescents in conflict with the law, in Cuiabá, Mato Grosso. To reach the proposed objectives, we chose the qualitative method, using primary data produced from direct observation, informal conversations and semi-structured individual interviews with 11 socio-educational agents that work in that institution. From the Goffmanian contribution, the Socio-educational Center was understood as Total Institution. The socioeducational agents work directly with the young offenders, performing activities of security of the institution, preservation of the inmates' integrity (physical and psychological), besides being responsible for accompanying them in pedagogical, legal (audiences), health and leisure activities. In a system of shifts, they experience the environment of a total institution that composes their daily life and, consequently, affects their lives, while at the same time contributing to reproduce it. The data were treated by the thematical analysis technique, and organized into six topics: Brief history of the Socio-educational System in Mato Grosso; About the socio-educational agent: characterization and insertion in Pomeri; The context of the socio-educational agent: about the male internment unit of the Pomeri Complex; 24 hours on duty; Perceptions of socio-educational agents and the attraction of the profession. The topics show the impact and difficulties experienced by the participants when they enter in the institution's staff; Disbelief in the process of socio-education and, in some moments, they feel like the adolescents, as victims of institutional neglect. These professionals describe the work environment as a dangerous place, capable of causing them health problems, besides contributing to change the social circle, limiting their leisure spaces. Even so, most refer to finding benefits in the permanence in the institution, pointing the regime of shifts and the salary as attractives of the profession. The socioeducational center can be understood, from the proposed reflections, as the scenario that composes the daily experiences of the socioeducational agents, so as to constitute their world of life.